China's Urban Pattern - Fang, Chuanglin (Springer Geography, 2018)
The book embarks on the tasks to systematically analyze the macro background of the spatial patterns of China's urban development, the theoretical foundations and framework, and its changing trajectory. From a quantitative perspective, we attempt to evaluate the rationale behind the spatial patterns of China's urban development and systematically simulate the various scenarios. From the simulation results, we propose the optimizing goals, priorities, models, and strategies for the spatial patterns of China's urban development. The work in this book attempts to provide constructive suggestions and potential strategies to support the effort to optimize the spatial patterns of China's urban development. It would be a valuable reference for planning departments, development and reform committees, and science and technology administrative departments at various governmental levels. It could also be a valuable addition to graduate students of urban planning, urban development, urban geography and relevant disciplines.